PBT (polybutylene terephthalate) modified material as well as preparation method and application thereof
By using core-shell structured coated flame retardant and hydrotalcite/zinc oxide in PBT modified materials, the odor and metal corrosion problems of halogen-free flame retardant PBT materials in automotive interior applications are solved, and the low odor, low corrosion and excellent performance of the material are achieved.
Patent Information
- Application Number
- CN202411925285.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing halogen-free flame retardant reinforced PBT materials are difficult to meet the needs when applied to automotive interiors, and are highly corrosive to metals and have reduced mechanical properties, making them difficult to meet the application requirements.
A coated flame retardant with a core-shell structure is used, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphate, and hydrotalcite and/or zinc oxide are added to the material to reduce metal corrosion and improve odor grades while maintaining excellent mechanical properties and flame retardant properties.
Halogen-free flame-retardant enhanced PBT modified materials with low odor, low metal corrosion, excellent mechanical properties and flame retardant properties are achieved, meeting the application needs of automotive interior materials.
Smart Images

Figure BDA0005209097270000101 
Figure BDA0005209097270000102 
Figure BDA0005209097270000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a PBT modified material and a preparation method and application thereof. Background Art
[0002] With the EU's restrictions on halogens in some products, halogen-free flame retardant materials are increasingly being promoted and applied. Alkyl phosphinate flame retardants are widely used halogen-free flame retardants. In PBT modification, the more mature material is the diethyl phosphinate aluminum flame retardant system. The flame retardant system of diethyl aluminum phosphinate and melamine polyphosphate can obtain good flame retardant properties at a low flame retardant addition level, and can also obtain better mechanical properties in the halogen-free flame retardant system.
[0003] However, there are currently two problems. The first is that the alkyl phosphinate flame retardant system has a relatively serious corrosion effect on metals, and is more corrosive to extruders, injection molding machines and equipment in the production chain. The second is that with the rise and development of new energy vehicles, the application of halogen-free flame retardant reinforced PBT materials is becoming more and more extensive, but the odor of halogen-free PBT materials used in automotive interiors is difficult to meet application requirements.
[0004] The prior art has proposed a solution to the first problem. For example, CN114605789A proposed to improve the corrosion of halogen-free flame retardant reinforced PBT to metal by adding basic magnesium sulfate whiskers. However, the mechanical properties of the product obtained by this solution are significantly reduced, and it is difficult to meet the requirements of the material for mechanical properties. As for the second problem, the prior art has not proposed an effective solution. Therefore, how to develop a halogen-free flame retardant reinforced PBT modified material with low odor, low metal corrosion and excellent mechanical properties has become a research hotspot. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a PBT modified material with low odor, low metal corrosion, excellent mechanical properties and flame retardant properties, and a preparation method and application thereof.
[0006] To achieve the above object, in a first aspect of the present invention, the present invention provides a PBT modified material, wherein the PBT modified material comprises the following components in parts by mass: 33-68 parts of PBT resin, 18-40 parts of glass fiber, 10-22 parts of flame retardant, and 0.08-0.49 parts of hydrotalcite and / or zinc oxide;
[0007] The flame retardant is a coated flame retardant with a core-shell structure, the core layer is melamine polyphosphate, and the shell layer is diethyl aluminum hypophosphite; the mass ratio of the shell layer to the core layer is ≥1;
[0008] The flame retardant has a TVOC of ≤300 μgC / g under the conditions of 180° C. and 60 min.
[0009] The present invention provides a PBT modified material in which a coated flame retardant having a specific TVOC (total volatile organic compound) content and a core-shell structure is introduced, and hydrotalcite and / or zinc oxide are selected for compounding. The obtained PBT modified material not only meets the halogen-free flame retardant properties, but also has low odor, low metal corrosion properties, and good mechanical properties.
[0010] Specifically, on the one hand, the present invention introduces a coated flame retardant with a core-shell structure, wherein the core layer is melamine polyphosphate and the shell layer is diethyl aluminum hypophosphite. The formed core-shell structure can significantly reduce the precipitation characteristics of melamine polyphosphate, thereby reducing the corrosiveness to metals; at the same time, the present invention further limits the TVOC content range of the coated flame retardant under the conditions of 180°C and 60 minutes, and can improve the odor level of the product on the basis of achieving low corrosiveness to metals, thereby obtaining a low-odor product; in addition, the present invention also limits the mass ratio of the shell layer to the core layer to ≥1, and when it is added as a flame retardant, the obtained product can meet the requirements of halogen-free flame retardancy; on the other hand, the present invention selects at least one of hydrotalcite and zinc oxide, and these two substances can cooperate with the coated flame retardant to improve the odor level of the product, reduce corrosion to metals and ensure the flame retardant level of the product, and can also avoid the degradation of PBT resin, thereby reducing the loss of mechanical properties of the product, and obtaining a product with excellent mechanical properties.
[0011] The testing method of the TVOC content of the flame retardant under the conditions of 180° C. and 60 min is obtained by referring to VDA277-1995.
[0012] Exemplarily, in the PBT modified material, the PBT resin may be any point value or any two point range values between 33-68 parts, such as 35-65 parts, or 33 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, etc.; the glass fiber may be any point value or any two point range values between 18-40 parts, such as 20-38 parts, or 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, etc.; the flame retardant may be any point value or any two point range values between 10-22 parts. The hydrotalcite and / or zinc oxide can be any point value or any two point range values between 0.08-0.49 parts, for example, it can be 0.1-0.4 parts, or it can be 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts, 0.28 parts, 0.3 parts, 0.32 parts, 0.35 parts, 0.38 parts, 0.4 parts, 0.42 parts, 0.44 parts, 0.46 parts, 0.48 parts, 0.49 parts, etc.
[0013] Preferably, in the PBT modified material, the mass percentage of PBT resin is ≥33%.
[0014] More preferably, in the PBT modified material, the mass percentage of PBT resin is between 48-55%.
[0015] Preferably, the intrinsic viscosity of the PBT resin is 0.66-1.30 dl / g. The intrinsic viscosity of the PBT resin is obtained by testing with reference to GB / T 14190-2017.
[0016] The present invention has no specific requirements for the intrinsic viscosity of the PBT resin, and a relatively good effect can be achieved within the intrinsic viscosity range of 0.66-1.30 dl / g given in the present invention. Exemplarily, the intrinsic viscosity of the PBT resin can be any point value or any two point range values between 0.66-1.30 dl / g, such as 0.66 dl / g, 0.70 dl / g, 0.75 dl / g, 0.80 dl / g, 0.85 dl / g, 0.90 dl / g, 1.00 dl / g, 1.05 dl / g, 1.10 dl / g, 1.15 dl / g, 1.20 dl / g, 1.25 dl / g, 1.30 dl / g, etc.
[0017] Preferably, the glass fiber is an alkali-free glass fiber. The present invention has no specific requirements on the fiber diameter, cross-sectional shape (such as round, flat, special-shaped, etc.), and fiber form (such as raw silk, coarse sand, ground, etc.) of the glass fiber.
[0018] Exemplarily, the mass ratio of the shell layer to the core layer can be any point value or any range of two points between ≥1, such as 1-2, 1-3, 1-5, 1-7, etc., or 1, 2, 3, 4, 5, 6, 7, etc.
[0019] As a preferred embodiment of the PBT modified material of the present invention, the mass percentage of hydrotalcite and / or zinc oxide is ≤0.9% based on the mass of the PBT resin.
[0020] Exemplarily, based on the mass of PBT resin, the mass percentage of hydrotalcite and / or zinc oxide can be any point value or any two point range value between ≤0.9%, for example, it can be 0.1-0.9%, 0.3-0.9%, 0.5-0.9%, 0.3-0.9%, 0.7-0.9%, etc., or it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, etc.
[0021] Preferably, based on the mass of the PBT resin, the mass percentage of the hydrotalcite and / or zinc oxide is ≤0.7%.
[0022] The present invention has been found that the mass percentage range of hydrotalcite and / or zinc oxide in PBT resin will affect the comprehensive performance of the product. When the mass percentage of hydrotalcite and / or zinc oxide in PBT resin is too high, the PBT resin will be degraded, thereby reducing the mechanical properties of the product. Therefore, when the mass percentage of hydrotalcite and / or zinc oxide is limited to 0.9% or less based on the mass of PBT resin, especially when the mass percentage of hydrotalcite and / or zinc oxide is 0.7% or less, the comprehensive performance of the obtained product is better.
[0023] As a preferred embodiment of the PBT modified material of the present invention, the mass percentage of hydrotalcite and / or zinc oxide is ≥0.9% based on the mass of the flame retardant.
[0024] Exemplarily, based on the mass of the flame retardant, the mass percentage of hydrotalcite and / or zinc oxide can be any point value or any two point range value between ≥0.9%, for example, it can be 0.9-4.2%, 0.9-2.4%, 0.9-1.5%, 0.9-1.0%, etc., or it can be 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, etc.
[0025] Preferably, based on the mass of the flame retardant, the mass percentage of the hydrotalcite and / or zinc oxide is ≥ 1.0%.
[0026] The present invention has found that the mass percentage of hydrotalcite and / or zinc oxide in the flame retardant will affect the odor level and metal corrosion of the product. When the amount of the acid absorber added is too small, it cannot produce effective synergy with the flame retardant, thereby improving the odor level of the product to a certain extent and the degree of metal corrosion also shows an increasing trend; when the mass percentage of hydrotalcite and / or zinc oxide is ≥0.9% based on the mass of the flame retardant, especially when the mass percentage of hydrotalcite and / or zinc oxide is ≥1.0%, the comprehensive performance of the obtained product is more excellent.
[0027] As a preferred embodiment of the PBT modified material of the present invention, the mass ratio of the core layer to the shell layer is 1.8-5.2.
[0028] It should be noted that the test method for the mass ratio of the core layer and the shell layer of the flame retardant can be determined by measuring the aluminum content in diethyl aluminum hypophosphite, deducing the mass of the shell layer, and subtracting the weight of the shell layer from the total weight to obtain the mass of the core layer, and then obtaining the mass ratio of the core layer and the shell layer. The aluminum element is obtained by ICP (inductively coupled plasma mass spectrometry) testing, and the mass percentage of aluminum element in diethyl aluminum hypophosphite is 6.92%.
[0029] Exemplarily, in the flame retardant, the mass ratio of the shell layer to the core layer can be any point value or any two point range values between 1.8-5.2, for example, it can be 2-5, or it can be 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, etc.
[0030] The present invention has found that the mass ratio of the shell layer to the core layer in the flame retardant will affect the odor level and corrosiveness to metals of the product. When the mass ratio of the shell layer to the core layer in the flame retardant is further selected to be 1.8-5.2, the comprehensive performance of the obtained product is better.
[0031] Preferably, the flame retardant can be prepared by any method known in the art for preparing a core-shell structure, such as a solution method, a gas phase method, a template method, etc. The present invention has no limitation on the preparation method of the flame retardant, and any coated flame retardant that can form a core-shell structure can achieve the effect of the present invention.
[0032] Exemplarily, the preparation method of the coated flame retardant may be:
[0033] (1) dispersing melamine polyphosphate in water to obtain a melamine polyphosphate suspension;
[0034] (2) adding a diethyl hypophosphite aqueous solution to a melamine polyphosphate suspension, and then adding an aluminum compound aqueous solution, followed by a coating reaction;
[0035] (3) Filter the system after the coating reaction, collect the filter residue, wash and dry it, and obtain the coated flame retardant.
[0036] Preferably, in the melamine polyphosphate suspension, the mass volume ratio of melamine polyphosphate to water is 1 g: (1-100) mL.
[0037] Preferably, in the diethyl hypophosphite aqueous solution, the mass percentage of diethyl hypophosphite is 20-50%.
[0038] Preferably, the mass percentage of the aluminum-containing compound in the aluminum-containing compound aqueous solution is 30-60%.
[0039] Preferably, in step (2), the coating reaction temperature is 30-90°C.
[0040] Exemplarily, the diethyl hypophosphite includes sodium diethyl hypophosphite; and the aluminum-containing compound includes aluminum sulfate.
[0041] Furthermore, the present invention removes volatile organic matter from the prepared coated flame retardant until its TVOC is ≤300μgC / g when tested at 180°C for 60 minutes; wherein the removal method is to carry out devolatilization for 2-4 hours at a vacuum degree of ≤100Pa and a temperature of 160-220°C until the TVOC value obtained by testing at 180°C for 60 minutes reaches a specific value.
[0042] As a preferred embodiment of the PBT modified material of the present invention, the flame retardant has a TVOC of ≤280 μgC / g under the conditions of 180° C. and 60 min.
[0043] Exemplarily, the TVOC of the flame retardant at 180°C and 60 min may be any point value or any two point range values between ≤280 μgC / g, such as 170 μgC / g, 178 μgC / g, 190 μgC / g, 200 μgC / g, 215 μgC / g, 220 μgC / g, 225 μgC / g, 230 μgC / g, 235 μgC / g, 240 μgC / g, 245 μgC / g, 250 μgC / g, 255 μgC / g, 260 μgC / g, 265 μgC / g, 270 μgC / g, 275 μgC / g, 277 μgC / g, etc.
[0044] The present invention finds that the TVOC of the flame retardant at 180°C and 60 min not only affects the odor level of the product, but also affects the product's corrosion to metal. When the TVOC of the flame retardant at 180°C and 60 min is further selected to be ≤280 μgC / g, the obtained product has a better odor level and lower corrosion to metal.
[0045] As a preferred embodiment of the PBT modified material of the present invention, the mass ratio of the hydrotalcite to zinc oxide is (1.5-6):1.
[0046] Exemplarily, in the acid scavenger, the mass ratio of hydrotalcite to zinc oxide can be any point value or any two point range values between (1.5-6):1, for example, it can be (2-6):1, or it can be 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, etc.
[0047] The present invention has found that when the mass ratio of hydrotalcite to zinc oxide is further selected to be (1.5-6):1, the comprehensive performance of the obtained product is better.
[0048] As a preferred embodiment of the PBT modified material of the present invention, the PBT modified material further comprises 0.1-5 parts of a processing aid.
[0049] As a preferred embodiment of the PBT modified material of the present invention, the processing aid includes at least one of an antioxidant, a lubricant, a nucleating agent, a laser aid, and a weathering agent.
[0050] Exemplarily, the antioxidant includes at least one of tetrakis[β(3.5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, pentaerythritol tetrakis(3-laurylthiopropionate), and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester; the lubricant includes at least one of pentaerythritol fatty acid ester, oxidized polyethylene wax, and silicone; the nucleating agent includes Klein's Na + The invention discloses a method for preparing the invention of the present invention comprising: preparing the invention comprises at least one of salt LICOMONT NAV101 PWD, Honeywell's zinc ion ionomer 295A, and talc powder with a mesh size of 3000-5000; the laser auxiliary agent comprises at least one of basic copper phosphonate, a polymer of antimony trioxide and polyamide coated with a metal oxide, a mixture of titanium oxide and a pigment; the weathering agent comprises at least one of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-bis(a,a-dimethylbenzyl)phenyl)benzotriazole, and bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate.
[0051] In a second aspect of the present invention, the present invention provides a method for preparing the PBT modified material, the preparation method comprising the following steps:
[0052] The dried raw materials are weighed, mixed and sent into a twin-screw extruder, and subjected to extrusion, strand drawing, cooling, pelletizing and drying to obtain a PBT modified material.
[0053] As a preferred embodiment of the preparation method of the present invention, the feeding rate of the twin-screw extruder is 350-550kg / h; the temperatures of each section of the screw of the twin-screw extruder from the feeding port to the die are 160-180°C, 230-260°C, 230-260°C, 230-260°C, 210-250°C, 210-250°C, 200-240°C, 200-240°C, 200-240°C, 200-240°C, and the screw speed is 350-600rpm.
[0054] In the third aspect of the present invention, the present invention provides the use of the PBT modified material in the preparation of materials in the electronic and electrical and automotive fields.
[0055] For example, the PBT modified material is used in the preparation of materials such as relays and cooling fans in the electronic and electrical fields, and in the preparation of materials such as new energy vehicle air-conditioning controllers in the automotive field.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The present invention provides a PBT modified material, in which a coated flame retardant having a core-shell structure and a specific TVOC content is introduced, and hydrotalcite and / or zinc oxide are selected, and the two cooperate with each other, so that the obtained PBT modified material has good mechanical properties and flame retardancy on the basis of low odor and low metal corrosion. At the same time, the preparation method of the PBT modified material provided by the present invention is simple, which is conducive to practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the metal corrosion test process;
[0059] Figure 2 This is a schematic diagram of the level I corrosion results in the metal corrosion test;
[0060] Figure 3 This is a schematic diagram of the Level II corrosion results in the metal corrosion test;
[0061] Figure 4 This is a schematic diagram of the level III corrosion results in the metal corrosion test;
[0062] Figure 5 This is a schematic diagram of the Level IV corrosion results in the metal corrosion test. DETAILED DESCRIPTION
[0063] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0064] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0065] PBT-1: PBT GX121, intrinsic viscosity 1.00 dl / g, Sinopec Asset Management Co., Ltd. Yizheng Branch;
[0066] PBT-2: PBT GL236, intrinsic viscosity 1.28dl / g, Sinopec Yizheng Chemical Fiber;
[0067] Fiberglass: ECS11-4.5-534A, Jushi Group;
[0068] Flame retardant 1: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 2:1; the TVOC under the conditions of 180℃ and 60min is 215μgC / g; homemade;
[0069] Flame retardant 2: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 3:1; the TVOC under the conditions of 180℃ and 60min is 277μgC / g; homemade;
[0070] Flame retardant 3: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 1:1; the TVOC under the conditions of 180℃ and 60min is 211μgC / g; homemade;
[0071] Flame retardant 4: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 5:1; the TVOC under the conditions of 180℃ and 60min is 217μgC / g; homemade;
[0072] Flame retardant 5: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 2:1; the TVOC under the conditions of 180℃ and 60min is 298μgC / g; homemade;
[0073] Flame retardant 6: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 2:1; the TVOC under the conditions of 180℃ and 60min is 178μgC / g; homemade;
[0074] Flame retardant 7: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 2:1; the TVOC under the conditions of 180℃ and 60min is 342μgC / g; homemade;
[0075] Flame retardant 8: coated flame retardant, the core layer is melamine polyphosphate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 0.5:1; the TVOC under the conditions of 180℃ and 60min is 219μgC / g; homemade;
[0076] Flame retardant 9: coated flame retardant, the core layer is melamine cyanurate, the shell layer is diethyl aluminum hypophosphite, the mass ratio of the shell layer to the core layer is 2:1; the TVOC under the conditions of 180℃ and 60min is 213μgC / g; homemade;
[0077] Flame retardant 10: diethyl aluminum hypophosphite, commercially available; TVOC at 180°C, 60 min is 210 μgC / g;
[0078] Flame retardant 11: melamine polyphosphate, commercially available; TVOC at 180°C, 60 min is 216 μgC / g;
[0079] Hydrotalcite: DHT-4A-2, Kyowa Chemical Industry Co., Ltd.;
[0080] Zinc oxide: commercially available;
[0081] Magnesium oxide: commercially available;
[0082] Lubricant: Pentaerythritol fatty acid ester, commercially available;
[0083] Antioxidant, pentaerythritol tetrakis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, commercially available;
[0084] The antioxidant and lubricant used in the parallel experiments of the embodiment and the comparative example are consistent;
[0085] The flame retardants 1-8 used were homemade, and the preparation method was as follows:
[0086] (1) dispersing melamine polyphosphate in water (the mass volume ratio of melamine polyphosphate to water is 1 g:4 mL) to obtain a melamine polyphosphate suspension;
[0087] (2) adding an aqueous solution of sodium diethyl hypophosphite (the mass percentage of sodium diethyl hypophosphite in the aqueous solution is 30%) to the melamine polyphosphate suspension, and then adding an aqueous solution of aluminum sulfate (the mass percentage of aluminum sulfate in the aqueous solution is 50%) to carry out a coating reaction at 70° C.;
[0088] (3) filtering the system after the coating reaction, collecting the filter residue, washing and drying it, and then placing the dried product under a vacuum degree of 100 Pa and a temperature of 200° C. for devolatilization for 2-4 hours, and then taking it out and testing its TVOC content under the conditions of 180° C. and 60 minutes to obtain the corresponding flame retardant;
[0089] The difference in the mass ratio of the core layer and the shell layer in the flame retardant is achieved by controlling the addition amount of melamine polyphosphate and diethyl sodium hypophosphite during the preparation process; the difference in the TVOC content in the flame retardant is achieved by controlling the devolatilization time;
[0090] The preparation method of flame retardant 9 is the same as that of flame retardant 1, except that melamine polyphosphate is replaced by melamine cyanurate;
[0091] Flame retardant 10-11: The commercially available product was placed in a vacuum of 100 Pa and a temperature of 200°C for devolatilization for 2-4 hours, and then taken out and tested for its TVOC content at 180°C for 60 minutes to obtain the corresponding flame retardant.
[0092] Examples 1-14 and Comparative Examples 1-7
[0093] The embodiments of the present invention and the comparative examples provide a PBT modified material, the components (mass parts) of the PBT modified material are shown in Tables 1-3; wherein V1 represents the mass percentage of the acid absorber to the flame retardant, and V2 represents the mass percentage of the acid absorber to the PBT resin;
[0094] Table 1
[0095] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 PBT-1 53 35 65 53 53 53 53 53 Flame retardant 1 16 12 20 16 16 16 16 16 Hydrotalcite 0.16 0.08 0.32 0.1 0.32 0.24 / 0.2 Zinc Oxide 0.08 0.04 0.16 0.05 0.16 / 0.24 0.04 Fiberglass 30 20 38 30 30 30 30 30 Antioxidants 0.5 0 0.5 0.5 0.5 0.5 0.5 0.5 Lubricants 0.5 0 0.5 0.5 0.5 0.5 0.5 0.5 V1 / % 1.5 1.0 2.4 0.9 3.0 1.5 1.5 1.5 V2 / % 0.5 0.3 0.7 0.3 0.9 0.5 0.5 0.5
[0096] Table 2
[0097]
[0098]
[0099] Table 3
[0100]
[0101]
[0102] The preparation method of the PBT modified material provided in Example 1 comprises the following steps:
[0103] The dried raw materials are weighed and mixed, and then fed into a twin-screw extruder for extrusion, strip drawing, cooling, pelletizing and drying to obtain a PBT modified material; wherein the feeding rate of the twin-screw extruder is 500 kg / h; the temperatures of each section of the screw of the twin-screw extruder from the feeding port to the die are 160°C, 250°C, 240°C, 230°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C, and the screw speed is 450 rpm.
[0104] The preparation methods of the PBT modified materials provided in Examples 2-14 and Comparative Examples 1-7 are consistent with that in Example 1, and if there are no relevant components, no relevant components are added.
[0105] Effect example
[0106] The effects of the present invention are as follows:
[0107] 1. TVOC test: refer to VDA277-1995, the test conditions are 120℃, 2h;
[0108] 2. Odor level: The test was conducted in accordance with PV3900. The odor level scores are shown in Table 4. The test was conducted by 5 people. Each person's test score was taken in intervals of 0.5 points, such as 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, etc. The final test result was the average value.
[0109] Table 4
[0110] Score evaluate 1 Can't feel 2 Perceptible, unobstructed 3 It's noticeable, but not too much of a hindrance. 4 Hindering 5 There is a greater hindrance 6 Unbearable
[0111] 3. Metal corrosion: Take the same mass (50g) of plastic particles, 10mL of ultrapure water, and metal sheets of the same cross-sectional area, and place them separately in a closed container. The container with ultrapure water and metal sheets is left open. The test condition is 85℃. The test process is as follows: Figure 1 As shown in the figure, after 6 days, the metal surface corrosion was observed and divided into grades Ⅰ, Ⅱ, Ⅲ and Ⅳ. Grade Ⅰ means that the metal surface is almost free of corrosion, grade Ⅱ means that the metal surface has slight rust, grade Ⅲ means that the metal surface has spot-like corrosion, and grade Ⅳ means that the metal surface has larger spot-like or flaky corrosion. The schematic diagrams of grade Ⅰ, Ⅱ, Ⅲ and Ⅳ corrosion are shown in the figure below. Figure 2-5 As shown;
[0112] 4. Tensile strength: Tested according to ISO 527-2-2012, the sample size is 150*10*4mm, and the tensile speed is 10mm / min;
[0113] 5. Flame retardant grade: tested in accordance with UL 94, with a specimen thickness of 0.75 mm;
[0114] The results obtained from the above performance tests are recorded in Table 5;
[0115] Table 5
[0116]
[0117] It can be seen from Table 5 that when the preparation method provided by the present invention is adopted, the obtained PBT modified material has the characteristics of low odor, low metal corrosion and good mechanical properties on the basis of having the basic flame retardant grade; specifically, the TVOC of the obtained product is below 286 μgC / g, the odor grade score is below 4.2 points, the metal corrosion grade is below grade II, and the tensile strength is above 105.5 MPa;
[0118] It can be seen from Examples 1-5 and Comparative Example 2 that the mass fraction of the components and the relationship between the addition amounts of the components will affect the comprehensive performance of the product to a certain extent. When the mass fraction of hydrotalcite and / or zinc oxide in Comparative Example 2 is too much, the tensile strength of the obtained product is significantly reduced, and the odor level also shows an increasing trend;
[0119] It can be seen from Example 1 and Comparative Example 1 that when no hydrotalcite and / or zinc oxide is added in Comparative Example 1, the odor level of the obtained product drops to 4.8 points, and the metal corrosion is level IV; it can be seen from Example 1, Examples 6-8 and Comparative Example 3 that the selection of hydrotalcite and / or zinc oxide will also affect the performance of the product, and when both hydrotalcite and zinc oxide are contained, the comprehensive performance of the obtained product is more excellent; when the hydrotalcite and / or zinc oxide used in Comparative Example 3 are not those of the present invention, the odor level of the obtained product drops to 4.5 points, and the metal corrosion is level IV;
[0120] It can be seen from Example 1, Examples 9-14 and Comparative Examples 4-7 that the type of flame retardant will also affect the performance of the product. When the TVOC of the flame retardant at 180°C and 60 min in Comparative Example 4 is not within the range given by the present invention, the TVOC of the obtained product is significantly increased, the odor level is reduced to 4.5 points, and the metal corrosion is Class III; when the mass ratio of the core layer and the shell layer in the flame retardant in Comparative Example 5 is not within the range of the present invention, the metal corrosion and flame retardancy of the obtained product are significantly deteriorated; when the core layer material of the flame retardant in Comparative Example 6 is not selected by the present invention, the metal corrosion of the obtained product is Class IV and the flame retardancy is V-2; when no coated flame retardant is formed in Comparative Example 7, the odor level of the obtained product is reduced to 5.0 points, and the metal corrosion is Class IV.
[0121] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PBT modified material, characterized in that: The PBT modified material comprises the following components in parts by mass: 33-68 parts of PBT resin, 18-40 parts of glass fiber, 10-22 parts of flame retardant, 0.08-0.49 parts of hydrotalcite and / or zinc oxide; The flame retardant is a coated flame retardant with a core-shell structure, the core layer is melamine polyphosphate, and the shell layer is diethyl aluminum hypophosphite; the mass ratio of the shell layer to the core layer is ≥1; The flame retardant has a TVOC of ≤300 μgC / g under the conditions of 180° C. and 60 min.
2. The PBT modified material according to claim 1, characterized in that: Based on the mass of the PBT resin, the mass percentage of the hydrotalcite and / or zinc oxide is ≤0.9%.
3. The PBT modified material according to claim 1, characterized in that: Calculated on the mass of the flame retardant, the mass percentage of hydrotalcite and / or zinc oxide is ≥ 0.9%.
4. The PBT modified material according to claim 1, characterized in that: The mass ratio of the shell layer to the core layer is 1.8-5.
2.
5. The PBT modified material according to claim 1, characterized in that: The flame retardant has a TVOC of ≤280 μgC / g under the conditions of 180° C. and 60 min.
6. The PBT modified material according to claim 1, characterized in that: The mass ratio of the hydrotalcite to zinc oxide is (1.5-6):
1.
7. The PBT modified material according to claim 1, characterized in that: The PBT modified material also includes 0.1-5 parts of a processing aid.
8. The PBT modified material according to claim 7, characterized in that: The processing aid includes at least one of an antioxidant, a lubricant, a nucleating agent, a laser aid, and a weathering agent.
9. The method for preparing the PBT modified material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain a PBT modified material.
10. Use of the PBT modified material according to any one of claims 1 to 8 in the preparation of materials in the fields of electronics, electrical engineering and automobiles.
Citation Information
Patent Citations
Halogen-free and phosphorus-free PBT enhanced composite material and preparation method thereof
CN104231575A
Low-mold-scale halogen-free flame-retardant PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof
CN115197551A
Halogen-free flame retardant as well as preparation method and application thereof
CN115505172A
Halogen-free flame-retardant nylon material for battery pack shell and preparation method of halogen-free flame-retardant nylon material
CN115785663A
PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof
CN117304663A